2004
DOI: 10.1159/000080659
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mast Cell Activation via Human IgG1 and IgG4

Abstract: Background: We have reported that canine mastocytoma-derived CM-MC cells are activated via canine IgG and express a high-affinity IgG receptor (canine FcγRI). The predicted amino acid sequence of the canine FcγRI α subunit was found to be 72% similar to that of humans. These results suggest that canine FcγRI have binding activity with human IgG and led us to investigate CM-MC activation via canine FcγRI and human IgG. Methods: The binding of human IgG to canine FcγRI was examined by flow cytometry using FITC-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In humans and rodents, IgG antibodies can also bind to various IgG receptors (FcγRs) on mast cells and activate or inhibit degranulation depending on the receptor [7,21,22]. IgG binding to canine mast cells via Fcγ-receptors has also been reported [23]. In our experiments using six healthy horses, an immediate skin reaction was induced in all horses by anti-IgE134 and in five out of six horses by the anti-IgG(T) antibody CVS40.…”
Section: Discussionmentioning
confidence: 53%
“…In humans and rodents, IgG antibodies can also bind to various IgG receptors (FcγRs) on mast cells and activate or inhibit degranulation depending on the receptor [7,21,22]. IgG binding to canine mast cells via Fcγ-receptors has also been reported [23]. In our experiments using six healthy horses, an immediate skin reaction was induced in all horses by anti-IgE134 and in five out of six horses by the anti-IgG(T) antibody CVS40.…”
Section: Discussionmentioning
confidence: 53%
“…Taken together, it was shown that CqTX-A caused a mixed venom immune reaction, although the precise mechanisms remain unknown. In particular, it is not known whether IgG (IgG 4 ) is involved in the late-phase reaction or if it reflects the repeated sting injury [24,25]. IgG 1 has been found to be involved in systemic anaphylaxis in a mouse model [26] and in the late asthmatic response in an epidemiological survey [27].…”
Section: Discussionmentioning
confidence: 99%
“…IgG 1 has been found to be involved in systemic anaphylaxis in a mouse model [26] and in the late asthmatic response in an epidemiological survey [27]. It has also been recognized in canine mast cell activations [25]. The pathogenesis caused by the venom from wasp and bee stings and that of aspergillosis or anisakis disease cannot be explained by allergic or toxic reactions alone.…”
Section: Discussionmentioning
confidence: 99%
“…The BR cells have been used to examine the ability of malignant mast cells to respond to various chemicals (Garcia et al, 1998), while the CM-MC cells have been used to demonstrate that mast cells can degranulate upon cross-linking of human IgG1 or IgG4 bound to the low-affinity IgG receptor (Sato et al, 2004). Both the C2 and BR cells possess KIT mutations in the juxtamembrane domain that cause constitutive activation, and as such these lines have been used to explore the use of targeted therapeutics directed at KIT inhibition (Liao et al, 2002; London et al, 1999; Ma et al, 1999).…”
Section: Discussionmentioning
confidence: 99%